Strategi Public Relations dalam Pemasaran di PT. Duta Putra Wisata Palembang - Hasbi, M.; Dwiyana, Sinta; Ibrahim, Ibrahim; Febriyanti, Febriyanti; Zulkipli, Zulkipli (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to analyze Public Relations Strategies in Marketing at PT. Duta Putra Wisata Palembang. The research focuses on how public relations strategies are implemented in the company’s marketing efforts, as well as the supporting and inhibiting factors in marketing the company to the public. This study was conducted at PT. Duta Putra Wisata Palembang using a descriptive qualitative research method. The informants in this research were public relations personnel, company leaders, and employees. Data was collected through observation, interviews, and documentation. Data analysis involved data reduction, data presentation, and drawing conclusions. The validity of the data was ensured using source triangulation and technique triangulation. The analysis results indicate that public relations strategies in marketing at PT. Duta Putra Wisata Palembang are being implemented but have not yet reached their full potential. Continuous improvements to the strategies in use are necessary. With optimized strategies, it is hoped that PT. Duta Putra Wisata Palembang will grow further and be able to compete with other companies